Transformasi Pengajaran Tata Bahasa Arab dalam Buku 'Maharah Lughawiyah' Karya Rusydi Ahmad Thu’aimah - Rochimul Umam; Nasiruddin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2024)
Abstract: Language is the primary tool in disseminating knowledge, intercultural communication, and the inheritance of civilization. Arabic language teaching is essential in education, especially in Islamic countries. In language teaching, the three key elements are sound, word, and structure, with grammar or